What your handwriting says about you - Edelhart, Mike. (Englewood Cliffs, N.J. : Prentice-Hall, 1979)
Provides the reader with basic techniques in handwriting analysis, presents samples of famous people to analyze, and discusses the use of analysts and analysis throughout history and in the field of crime today.
Dizin var.
Keywords: Graphology -- Juvenile literature; Graphology; Grafikoloji -- Çocuk edebiyatı; Grafikoloji